Work ethic: Religious and cultural values that encourage independence and the spirit of migration - Zuhri, Ach.; Riyadi, Slamet; Sihab, Muhammad (Edelweiss Applied Science and Technology, 2024)
The work ethic of the Madurese people is influenced by religious and cultural values, encouraging hard work, independence, and the spirit of wandering to achieve prosperity. Previous studies have shown that the high work ethic of Sukarara craftsmen is influenced by culture, religion, and self-actualization, but the results are limited to the local context. This study will reveal the unique work ethic of the Madurese people, rooted in cultural and religious values, creating a tenacious and adaptive attitude to achieve success amidst challenges. This qualitative research design uses in-depth interviews and ATLAS.ti for analysis, involving six informants with diverse backgrounds, to understand the work ethic of Madurese entrepreneurs. This study involved interviews with six Madurese entrepreneurs, highlighting their work ethic and income. The results show variations in income, with a strong work ethic as a key factor for success. The Sankey diagram illustrates the relationship between work ethic, social support, and positive attitudes. Madurese cultural values, such as persistence and responsibility, support the entrepreneurial spirit. The Theory of Planned Behavior shows the importance of attitudes, social norms, and perceived control in shaping work ethic. Cultural values and social support are crucial in shaping the work ethic of Madurese entrepreneurs. Further research needs to explore other variables that influence entrepreneurial success.